Understandng simulated long-term changes in the North Atlantic MOC - Latif, Mojib; Martin, Thomas; Reintges, A.; Martin, Torge; Park, Wonsun; Keenlyside, Noel (2011)
Future changes in the Atlantic meridional overturning circulation (MOC) will result from processes both internal and external to the climate system. Here, using the CMIP3 database and simulations with the Kiel Climate Model (KCM), three aspects of modelbased projections of the Atlantic MOC will be discussed: First, while most climate models predict a weakening of the North Atlantic meridional overturning circulation (MOC) during the twenty-first century, large uncertainty exists. Quantification of the different sources of uncertainty – external, internal and model – indicates model error is the largest component, internal variability is significant during the first decades, while scenario uncertainty is almost negligible. The different contributions to model uncertainty – wind and density, salinity versus temperature – will be also discussed. Second, individual studies suggest that multidecadal changes in the MOC are strongly related to large-scale salinity anomalies and therefore to changes in the surface freshwater fluxes and freshwater transport. Here, the general relationship between the MOC and freshwater budget of the Northern Hemisphere is analyzed for the twentieth and twenty-first centuries. Global warming leads to an implified hydrological cycle, which affects the vertical salinity and temperature profiles. The meridional changes in the oceanatmosphere interaction diminish the meridional oceanic density contrast. In the North Atlantic sinking regions, these changes are strongly related to salinity anomalies at the surface. We find in the multi-model mean a strong freshwater export from the Arctic into the northern part of the North Atlantic, stressing the importance of a realistic representation of the hydrological cycle in the models. Third, experiments with KCM indicate that ocean-sea ice-atmosphere interaction in the Southern Ocean could give rise to significant centennial scale changes in the MOC. The model simulates an internal mode of variability on a multi-centennial time-scale set by the ...